A Case Study on Grammatical Errors in Students' Descriptive Writing at Al Ghozali Senior High School - Y, Sunardi; Anwar, Mursyid (Universitas Pamulang, 2024)
The motivation behind this research stems from the observed challenges faced by high school students in mastering English grammar, particularly in writing. This study investigates the grammatical errors frequently made by tenth-grade students in their descriptive writing at Al Ghozali Senior High School, Gunung Sindur, Bogor. The primary objective is to analyze these errors to understand their nature and frequency, providing insights for more effective teaching strategies. This descriptive research utilizes a documentary analysis method, focusing on students' written works. The research subjects are tenth-grade students at Al Ghozali Senior High School. Data collection involved gathering students' descriptive essays, which were then analyzed using a checklist of common grammatical errors adapted from La Trobe University. The checklist includes categories such as subject-verb agreement, verb tense, word class, vocabulary, singular/plural, articles, sentence structure, spelling, and punctuation. Data analysis revealed that the most frequent errors involved subject-verb agreement (94.47%), followed by verb tense (66.66%) and word class (57.14%). Other common errors included vocabulary usage, singular/plural distinctions, and article usage. These findings highlight specific areas where students struggle the most, providing valuable information for educators. The implications of this research suggest that targeted interventions and continuous practice are essential for improving students' grammatical skills in writing. By addressing the identified errors, teachers can enhance their instructional methods, ultimately helping students achieve better proficiency in English writing. This study not only benefits students and teachers at Al Ghozali Senior High School but also offers insights for future research in similar educational contexts.